Figurative of Lo I Keta Spells in Society of Bima: A Riffaterre Semiotics Research - Kurniawan Kurniawan; Sholihin Sholihin; Mulyadi Mulyadi (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
The existence of cultural literacy can be observed in the typical language in the Lo I Keta spells which developed in the traditional Bima society. A broad understanding of society about the Lo I Keta spells language by substituting meaning in producing figures of speech. This research aims to describe the figure of speech in the Lo I Keta spells. The research of Riffaterre's semiotics becomes the basis for analyzing the replacement of meaning. The research approach is descriptive qualitative using data collection techniques such as recording, interviewing, and recording. The results show that figurative forms include metaphor, anaphora, epiphoria, parallelism, and symbolic.